UPANISHADS AND THEIR SIGNIFICANCE - Patel, Mahesh G.; Bariya, Pravinkumar Kalubhai (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In the present times, it has become a habit to live life by getting momentary pleasure through modern technology. But there is no time left to try to turn the pages of real life. Man has the power to think, understand, work more than other creatures. For this reason, he wants to know new things and keeps striving to do something. Today's man does not believe in self-satisfaction and remains immersed in an imaginary world created with his own thoughts. What is self-knowledge or Brahman knowledge for him? How much can the existence of how to live life be? What are the stages of life and how can they develop or decay? How can they be cured? How can happiness, peace and contentment be achieved? How can one experience perfection and bliss in life? How can one reconnect with the original essence from which this life has been achieved after being separated from it? The answers to these questions are given in detail in the Upanishads. Why are the texts (Upanishads) that have been collected in the past thousands of years of spiritual search experiences considered foremost and universally accepted even after thousands of years because they state the ultimate truth and that is not due to the logic of the intellect but because the sages themselves, after having personal experience, have said that the Parabrahman is the supreme and the four great verses that explain the Brahman-parak matter in different ways are the special seed and fruit of the Upanishads. In order to find true happiness and joy, one should go beyond all the thoughts and desires that arise by addressing the inert elemental body, the intellect and lust guided by narrow selfishness. What is the true nature of oneself and that world? In order to understand it, one should insist on understanding it, and in that self-experience, one should understand that in the contemplation of the pure one element, in the harmony of the soul, the soul and the Supreme Soul, there is the complete Parabrahman.